Unveiling Student Stress: Linking Self-Regulation in Learning to Academic Stress Amidst Online Education: Mengungkap Stres pada Mahasiswa: Menghubungkan Regulasi Diri dalam Pembelajaran dengan Stres Akademik di Tengah Pendidikan Online - Irawati, Ria; Fatmawati, Zaki Nur (Indonesian Journal of Education Methods Development, 2023)
In the context of the ongoing pandemic, where traditional in-person learning has shifted to online platforms, this quantitative correlation study investigates the relationship between self-regulation in learning and academic stress among students. The research involved a population of 380 students, with a sample size of 192 from SMAN 1 Wonoayu, selected through simple random sampling. The research hypothesis postulated a negative relationship between self-regulation in learning and academic stress. Analysis using Pearson's Product Moment correlation revealed a significant coefficient of r = -0.439 (p < 0.05), underscoring the inverse connection. The study found that self-regulation variables contributed significantly, accounting for 19.2% of academic stress variance. This study sheds light on the crucial role of self-regulation in mitigating academic stress during the transition to online education, thereby guiding educators and policymakers in enhancing students' learning experiences.Highlights: The pandemic-driven shift to online education has led to increased academic stress among students. This study establishes a negative correlation between self-regulation in learning and academic stress. Self-regulation contributes significantly (19.2%) to mitigating academic stress, emphasizing its vital role in online learning environments. Keywords: Online education, Self-regulation, Academic stress, Pandemic, Learning experiences